2021
DOI: 10.1126/scitranslmed.abb0192
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ascites- and tumor-infiltrating γδ T cells reveals distinct repertoires and a beneficial role in ovarian cancer

Abstract: The role of γδ T cells in antitumor immunity has been under investigation for the past two decades, but little is known about their contribution to clinical outcomes in patients. Here, we set out to define the clonotypic, phenotypic, and functional features of γδ T cells in peripheral blood, ascites, and metastatic tumor tissue from patients with advanced epithelial ovarian cancer. T cell receptor (TCR) sequencing of the γ chain revealed that tumor-infiltrating γδ T cells have a unique and skewed repertoire wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 67 publications
(86 reference statements)
2
37
1
Order By: Relevance
“…Identifying the Tex and Ttrm cells in all tumors (Methods) showed their respective rates were correlated between the two lineages (Pearson r = 0.8 in both cases) (Figure 2d). Confirming recent reports, [7][8][9] the majority of γδ TILs cancer-wide was of TCRVγnon-9 subtype, reflecting the extra-lymphoid tropism of this subset (Figure 2e, Table S2b). Combining trajectory and signature analyses revealed that, like Tex T CD8 TILs, all the Tex γδ TILs displayed Tem or Tcm 2e, f).…”
Section: Convergent Differentiations Of γδ T and T Cd8 Lymphocytes Infiltrating Tumorssupporting
confidence: 90%
See 2 more Smart Citations
“…Identifying the Tex and Ttrm cells in all tumors (Methods) showed their respective rates were correlated between the two lineages (Pearson r = 0.8 in both cases) (Figure 2d). Confirming recent reports, [7][8][9] the majority of γδ TILs cancer-wide was of TCRVγnon-9 subtype, reflecting the extra-lymphoid tropism of this subset (Figure 2e, Table S2b). Combining trajectory and signature analyses revealed that, like Tex T CD8 TILs, all the Tex γδ TILs displayed Tem or Tcm 2e, f).…”
Section: Convergent Differentiations Of γδ T and T Cd8 Lymphocytes Infiltrating Tumorssupporting
confidence: 90%
“…31 This repartition disappears in tumors, however, where the TCRVγnon9 γδ TILs predominate in all (non-)hematopoietic cancer types. [7][8][9] Viral infections are major drivers of peripheral differentiation of T CD8 and γδ T lymphocytes. Thus, the locally phased differentiation of both γδ T and T CD8 lymphocytes strongly suggests a functional convergence toward effective antitumor immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In human solid cancers, γδ tumour-infiltrating lymphocytes (TILs) have been proposed by many studies to be relevant prognostic factors; however, there appear to be differences in their anti-tumour functions across different solid cancer types. Notably, their tumour infiltration and cytolytic activity have been linked with a beneficial role for patient outcome in gastric cancer [ 121 , 122 ], hepatocellular carcinoma [ 68 ], ovarian cancer [ 123 ], colorectal cancer [ 124 , 125 ], renal cell carcinoma [ 126 , 127 ], glioblastoma [ 128 ] and triple-negative breast cancer [ 129 , 130 , 131 ]. On the other hand, they were also reported to have a negative impact on prognosis in ovarian cancer [ 37 ] and oral cancer [ 42 ], and conflicting studies also found them to positively correlate with pathogenesis in colon cancer [ 132 ] and breast cancer [ 133 , 134 ].…”
Section: Anti-tumour Functions Of γδ T Cellsmentioning
confidence: 99%
“…In human cancer, our research and other studies have shown that the abundance of γδ TILs, whether TCRVγ9 or TCRVγnon9, varies substantially across individuals and among cancer types, and that it is associated with patient outcomes [22,23]. As opposed to peripheral blood and hematopoietic malignancies dominated by TCRVγ9 γδ T cells, the predominant subset of γδ TILs in most solid tumors are TCRVγnon9 cells, whose number, cytotoxic differentiation, and functional status vary between individuals [24][25][26].…”
Section: Introductionmentioning
confidence: 60%